2012
DOI: 10.1016/j.neuron.2012.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Oscillations in the Thalamocortical System Induce Long-Term Neuronal Plasticity

Abstract: Summary Long-term plasticity contributes to memory formation and sleep plays a critical role in memory consolidation. However, it is unclear whether sleep slow oscillation by itself induces long-term plasticity that contributes to memory retention. Using in vivo pre-thalamic electrical stimulation at 1 Hz which itself does not induce immediate potentiation of evoked responses, we investigated how the cortical evoked response was modulated by different states of vigilance. We found that somatosensory evoked pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
211
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(220 citation statements)
references
References 50 publications
(63 reference statements)
6
211
3
Order By: Relevance
“…Chauvette et al (2012) showed that somatosensory cortical-evoked local field potentials are upregulated after the first epochs of NREMS [78]. Grosmark et al (2012) measured hippocampal firing rates during sequences of sleep stages [79].…”
Section: Novel Forms Of Synaptic Plasticitymentioning
confidence: 99%
“…Chauvette et al (2012) showed that somatosensory cortical-evoked local field potentials are upregulated after the first epochs of NREMS [78]. Grosmark et al (2012) measured hippocampal firing rates during sequences of sleep stages [79].…”
Section: Novel Forms Of Synaptic Plasticitymentioning
confidence: 99%
“…Interestingly, when a memory is being encoded indicating its importance for future use in a test appears to increase the likelihood of that memory being consolidated in sleep (Wilhelm et al 2011). Our understanding of specific memory functions and neurobiological processes in sleep is increasing, yet there remain many issues requiring further research (Chauvette, Seigneur, and Timofeev 2012;Grosmark et al 2012). …”
Section: Other Educational Considerationsmentioning
confidence: 99%
“…The importance of reactivation to memory is clear from these systems-level studies. Circuit reactivation in slice is remarkably similar to activity in vivo during SWA 25,26 and provides a useful tool to examine synaptic plasticity in this context 13 . We find that circuit reactivations in vitro display stereotyped spatiotemporal patterns of neuronal activity consistent with observations of replay in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…However, in contrast to classic experimental induction protocols, in vivo recordings show that reactivation of any one pattern of neuronal spikes is sparse and intermittent 2,4,5 . Recent work has demonstrated that slow-wave activity (SWA), which comprises UP and DOWN states, promotes long term potentiation (LTP), consistent with a role for SWA in memory consolidation 13,14 . However, linking endogenously generated spatiotemporal sequences and synaptic plasticity remains largely unexplored.…”
mentioning
confidence: 91%